2021
DOI: 10.1016/j.ijid.2021.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Duration of SARS-CoV-2 positive in quarantine room environments: A perspective analysis

Abstract: Objective To explore the duration of SARS-CoV-2 remained in the environment of quarantine hotels. Methods 39 Patients by RT-PCR were included. We collected the clinical features, laboratory test results, smear sample information, and quarantine room information. Genome sequencing and phylogenetic analysis were launched. We analyzed the factors associated with environmental contamination. Result Among 39 COVID-19 cases, 10 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…Our research showed that the Delta VOC was positive in samples mainly from toilets and bedside tables. The positive rates and surface distribution characteristics are in line with those previously reported (19,20). The environmental contamination by asymptomatic cases with positive anal swab results was also mainly concentrated in toilets, and there could have been a chain of transmission with mobile phones as a medium (14).…”
Section: Discussionsupporting
confidence: 88%
“…Our research showed that the Delta VOC was positive in samples mainly from toilets and bedside tables. The positive rates and surface distribution characteristics are in line with those previously reported (19,20). The environmental contamination by asymptomatic cases with positive anal swab results was also mainly concentrated in toilets, and there could have been a chain of transmission with mobile phones as a medium (14).…”
Section: Discussionsupporting
confidence: 88%
“…It was during an ongoing COVID-19 outbreak investigation on a ferry boat [40], during a COVID-19 outbreak on a cruise ship [49], during a COVID-19 outbreak in a nursing home [40], and during a local COVID-19 outbreak [50]. No specific information regarding the local or national epidemiological situation during the study period was found in four of the studies [51][52][53][54].…”
Section: Areas Surrounding Confirmed Covid-19 Cases In Non-healthcare Settingsmentioning
confidence: 99%
“…In one study, 50% of the 428 samples were taken before the cleaning and disinfection, and the other half was taken after the disinfection procedure [51]. No specific information regarding any prior treatment of surfaces was found in three studies [50,52,53]. The public availability of hand sanitizers was not described in any of the studies [40,[49][50][51][52][53][54].…”
Section: Areas Surrounding Confirmed Covid-19 Cases In Non-healthcare Settingsmentioning
confidence: 99%
“…The viable period of Human coronavirus 229 E (HCoV) in tap water was 10 days at 23 °C and more than 100 days at 4 °C, which was proved by virus culture in a previous study ( Gundy et al, 2008 ). The water cup was the most frequently contaminated site (2/2, 100 %) in another study conducted in China ( Liu et al, 2021 ). In this study, the water cup was also identified with contamination in room-temperature environments (1/2, 50 %), which is understandable because the patient's saliva has a high viral load and water in the cup may also play an important part in virus persistence.…”
Section: Discussionmentioning
confidence: 95%